Naturalization and Adaptation Taking Place in the Translation of Medical Texts from English into Indonesian - Sri Rwa Jayantini, I Gusti Agung Ayu (e-Journal of Linguistics; Vol 12 No 1 (2018): eJL-January, 2018)
This study investigates naturalization and adaptation as the translation procedures utilized in the translation of English medical texts into Indonesian. It aims at (1) identifying how naturalization takes place in English-Indonesian medical texts translation and (2) describing the adaptation of meaning reflecting the equivalence process in translation. The two translation procedures are specifically discussed concerning the phenomena that adaptation of form and meaning are irrefutable in the process of translating. Here, naturalization demonstrates the absorption of English medical terms into Indonesian reflecting the adjustment of the terms’ form namely spelling and pronunciation. Meanwhile, adaptation refers to the process of adapting the meaning of the foreign terms. This process involves the mapping of concepts contained in the terms and how they are commonly utilized in their field of study so that the equivalence can be obviously explained. The data were taken from the translation of selected articles from a medical textbook, General Ophthalmology (2008) and its translation into Indonesian Oftalmologi Umum . The results show that there are four classifications made in the mapping of naturalization of the English-Indonesian medical terms and adaptation occurs through the use of synonymous terms in the target language that are considered having similar meaning components with those of the terms in the target language.